Integration of Multicultural Folklore in Language Curriculum to Increase Intercultural Empathy - Wahyuni, Erna; Hussain, Sara (International Journal of Language and Ubiquitous Learning, 2025)
Background. Intercultural empathy is an essential skill in globalized societies, yet language education often overlooks its emotional and cultural dimensions. Multicultural folklore offers a rich and underutilized resource for embedding cultural narratives in language curricula to foster deeper cross-cultural understanding. Purpose. This study aims to investigate the effectiveness of integrating multicultural folklore into language learning to enhance students' intercultural empathy across five core dimensions: openness, empathy, respect, engagement, and confidence. Method. Using a quasi-experimental design, two groups of junior high school students (N=60) were observed over six sessions. The experimental group received a folklore-integrated language curriculum, while the control group followed a conventional language program. Data were collected through pretests, posttests, and student reflective journals, analyzed using descriptive statistics and thematic coding. Results. The experimental group showed a significant increase in empathy scores, with a mean gain of 11 points compared to 2 points in the control group. Reflective writings revealed enhanced emotional engagement, especially in students exposed to diverse cultural narratives. The empathy dimension showing the highest improvement was respect, followed by emotional empathy. Conclusion. Multicultural folklore is a powerful pedagogical tool for fostering intercultural empathy in language education. The integration of narrative elements into linguistic instruction enhances not only comprehension but also emotional connection and cultural sensitivity. Future research should explore broader cultural contexts and assess long-term impact.